An Exploration of The Perceptions Regarding Parental Involvement in The Academic Activities of Secondary School Students at City Kotli AJK (European Journal of Teaching and Education, 2020)
The world is becoming more and more competitive and the quality performance is the key for personal progress. Excellence particularly in academic and generally in all other areas has been seen as an important aspect. The good academic performance of the children is the strongest pillar in the building of a healthier community. The purpose of conducting this research study was to check and explore the involvement of parents in the academic activities of the students. A quantitative research approach was used for this study with class 10th present students of 15 government and private schools of Kotli City through random selection. Survey design was used for data collection by distributing two set of questionnaires to both parents and their children’s. After analysis of the data the researcher found that the involvement of parents in children’s education not only facilitates their children’s but also it significantly influenced nation as a whole. Thus, the research study recommends the parents to facilitate and provide the good learning environment to their children’s by showing involvement in children’s activities at home to educate the bright stars of the future more accurately towards the path of prosperity. This will help to increase the level of academic achievement of students.